SAT0225 Urinary monocyte chemoattractant protein-1 (UMCP1) in SLE, a biomarker of renal or more general disease?. (23rd January 2014) - Chew, C.; Pemberton, P.; Husain, A. Al-M.; Haque, S.; Bruce, I.N.
Abstract : Background: Monitoring SLE disease activity either globally or within individual organ systems is based on scoring methods and serological tests. Specific biomarkers to enhance and improve disease follow-up have been examined. Animal and human studies have proposed that monocyte chemoattractant protein 1 (MCP1) has a role in renal damage and nephritis in SLE. Studies have also linked increased urinary MCP1 (uMCP1) levels with active renal disease and the severity of nephritis. Although studies on urinary albumin (uAlb) in SLE are limited, microalbuminuria has been suggested to be reliable in the diagnosis and follow-up of lupus nephritis. Objectives: We aimed to compare uMCP1 and uAlb in SLE patients and healthy controls, and in SLE, those with and without lupus nephritis. We assessed if clinical, serological or vascular features in SLE were associated with uMCP1 and uAlb concentrations. Methods: We recruited SLE patients (≥4 ACR 1997 criteria) and healthy controls from clinics in Greater Manchester. Patients underwent clinical assessment of SLE disease activity (SLEDAI 2K) and damage (ACR/SLICC Damage Index (SDI)). Cardiovascular risk factors included blood pressure, body mass index (BMI), a fasting sample of lipid profiles and blood glucose. Baseline renal function was estimated using the modified Cockcroft-Gault and MDRD formulae. UMCP1, uAlb, serum VCAM-1 and E-selectin was measured with R & D Systems' ELISA. Results: We studied 178 patients and 68 controls with a median (IQR) age of 50 (39-60) and 53 (46-61) years old respectively. SLE patients were more likely to have hypertension (46.3% vs. 24.2%; p= 0.002). Within our SLE group, 38 (21.6%) had a history of lupus nephritis. UMCP-1 and uAlb were both significantly higher in SLE than in controls (114.7 (73.7-167.3) vs. 81.9 (46.5-125.1), p <0.001; 10.29 (6.27-22.31) vs. 7.87 (5.45-10.85), p =0.003, respectively]. UAlb was significantly higher in SLE patients with a history of lupus nephritis compared to those without (29.35 (9.12-54.78) vs. 9.05 (5.69-17.44); p= 0.0001), but uMCP-1 showed no difference in both groups (125.5 (70.89-200.3) vs. 113.9 (76.63-161.3), p= 0.399). In SLE, uMCP-1 correlated with uAlb (r, p ) (0.242, 0.001 ), but not with standard measures of renal function; uMCP-1 also correlated significantly with serum VCAM-1 levels (0.201, 0.008 ) but not E-selectin (-0.066, 0.394 ). There was no difference in uMCP-1 or uAlb in SLE patients with active disease (SLEDAI scores of ≥4 vs <4) nor did uMCP-1 correlate with dsDNA or complement levels at the time of assessment. The SDI was associated with increased uMCP1 ( p= 0.016). Conclusions: UMCP1 and uAlb are both increased in SLE compared to controls. While uAlb was related to a history of lupus nephritis, uMCP-1 was less specific for renal disease but reflected levels of overall lupus damage and its association with VCAM-1 suggests that it may also in part reflect overall levels of vascular activation in SLE patients. References: Alzaway A, et al. Int J Rheu Dis 2009;12:311-8 Bruce IN. Lupus 2005;14:687 Rovin B et al. J Am Soc Nephrol 2005:16:467-73 Disclosure of Interest: None Declared